UKRAINIAN TECHNICAL AND ECONOMIC INSTITUTE IN 1932–1952 - Olexandr Utkin (Київські історичні студії)
The article gives a detailed analysis of the main reasons which allowed to create the Ukrainian Technical and Economic Institute of Distance Learning. It was formed by scientists, public figures of emigrants. The Institute carried out the work in Czechoslovakia and Germany in the 1930s-50s. It was being formed in the difficult conditions of the international economic crisis. In this way the socio-economic and cultural sphere of European countries, the nature and content of the activities of the diaspora scientific and educational structures were influenced on.The newly created Institute formed a system of correspondence training for agricultural workers in comparison with the Ukrainian Academy of Economics. There were found non-state independent ways of financing the educational and research process to write and publish a methodological literature, the textbooks. The students and lectures got opportunity to participate in scientific forums. Overcoming the difficulties of the occupation of Czechoslovakia during the Second World War when the activity of the Institute was meticulously controlled by the police, the Gestapo, a censorship. It braked and suspended the educational work. In spite of this fact it could not deprive Ukrainian students of the desire to study. As a result the student’s emigrant community of the High School was saved and replenished. After the end of World War II the Institute moved to the territory of Germany. The Ukrainian Technical and Economic Institute of Distance Learning was expanded. There were five high school departments, a network of technical schools, secondary and lower secondary schools and courses, training skilled personnel for agricultural and industrial production. In 1952 the Institute was relocated to the United States of America. There it functioned as a research institution.